Conference on Rural Industries Projects 26th to 30th July, 1963 - Planning Commission (Planning Commission, 1963)
The Rural Industries Projects Conference met on 26th and 27th July and 29th and 30th July, 1963. During the first two days, viz, 26th and 27th, the Conference was attended by officials from State Governments and the concerned Ministries of the Government of India, representatives from All India Boards/ Commission concerned with the development of village and small industries, Reserve Bank of India, State Bank of India and members of the Rural Industries Planning Committee and its Standing Committee and some members of the Planning Commission, etc. On 29th and 30th July, the Conference was attended by Chief Ministers and Ministers in charge of rural industries from various States besides these present on the first two days .
Planning Commission (Rural Industries Planning Committee)
Planning Commission
Keywords: Rural Industries Projects; Rural Industries Planning Committee; Standing Committee; Planning Commission; Ministry of Commerce & Industry; Central Small Industries Organisation; International Labour Organisation